Management of Soil Fertility for Sustaining Quality Mulberry Leaf Production in North India - Rathore, M.S.; Srinivasulu, Y. (International Journal of Scientific Research in Biological Sciences, 2018)
The silk industry in Jammu and Kashmir (J&K) state is of very ancient origin. Due to natural irrigation system and highly salubrious climatic conditions is very suitable for bivoltine sericulture. Soil fertility is only one of a number of factors that determine the magnitude of crop yield. Low fertility results in decreased crop development and yield. The fertility of the soil can be managed by fertilization or by application of appropriate management approach. Plants sequester nutrients from atmosphere via photosynthesis and absorption by roots from soil, proportion of which in turn is taken up by animals and returned back to soil. The soil microbial biomass is the living portion of organic content in soil, maintenance of which facilitates retention of soil organic pool and nutrient availability. Increasing organic carbon in soil improves soil health, reduces soil erosion and degradation, improves surface water quality, and increases soil productivity. Indiscriminate use of inorganic fertilizers may have deteriorated the soil characteristics and its micro-flora. In view of above reasons, the output yields of mulberry are low in the traditional sericulture zones. Application of green technologies will pave way for sustenance of soil fertility and quality leaf production.